2018
DOI: 10.1007/s13592-018-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive DNAs in Melipona scutellaris (Hymenoptera: Apidae: Meliponidae): chromosomal distribution and test of multiple heterochromatin amplification in the genus

Abstract: Melipona bees are remarkable due to the high contrast in heterochromatin amounts, making this group interesting for studying repetitive DNA amplification. Here, we performed the first efforts for the chromosomal localization of different repetitive DNAs in M. (Michmelia) scutellaris and tested for unique or multiple heterochromatin amplification in Melipona subgenera. Our data revealed enrichment of repetitive DNAs in chromosomal heterochromatic arms demonstrated by C 0 t-DNA and DOP-PCR probe hybridization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
(44 reference statements)
5
15
1
Order By: Relevance
“…Microsatellite hybridization was observed in the DAPI-negative portion corresponding to euchromatin. Similar results have been obtained in other Meliponini studies [Ferreira, 2015;Piccoli et al, 2018;Travenzoli et al, 2019b]. The microsatellite probes bound and marked the chromosomes in all species tested ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Microsatellite hybridization was observed in the DAPI-negative portion corresponding to euchromatin. Similar results have been obtained in other Meliponini studies [Ferreira, 2015;Piccoli et al, 2018;Travenzoli et al, 2019b]. The microsatellite probes bound and marked the chromosomes in all species tested ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…Considering that heterochromatin in Meliponini arose at different times [Cunha et al, 2018;Piccoli et al, 2018;Pereira, 2018] and that chromatin with intermediate staining was observed only in species with centromeric heterochromatin, this "new class" of chromatin can indicate the beginning of the process of heterochromatinization in these species, and will result in the formation of completely heterochromatic arms as seen in high frequency in the Meliponini. Therefore, the verification of the existence of a new class of chromatin with intermediate staining intensity, between that of the euchromatin and heterochromatin, demonstrates a possible path of how karyotype evolution has taken place in the tribe Meliponini.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3b, d), as already reported for the two colonies analysed by Rocha et al (2007). The presence of a unique autosome pair with a nucleolus organizer in M.quinquefasciata corroborated previous reports about the location of the rDNA clusters in other Melipona species, independent of the technique used (Ag-NOR impregnation, CMA 3 staining or FISH; Rocha et al 2002, Brito et al 2003, Lopes et al 2011, Cunha et al 2018, Piccoli et al 2018). This seemed to be the most frequent pattern found in other Meliponini genera (Brito-Ribon et al 1999, Rocha et al 2003, Krinski et al 2010), although the presence of multiple rDNA clusters has also been described (Rocha et al 2003, Brito et al 2005, Duarte et al 2009, Martins et al 2009, Godoy et al 2013).…”
Section: Resultssupporting
confidence: 88%
“…Cytogenetic analyses, in particular, are an important tool for understanding the macro-scale genomic organization of different any species. These analyses comprise descriptions of chromosome number [11], [2], [9], heterochromatin distribution patterns [12], characterization of AT and CG rich regions [13], [12], localization of 18S ribosomal genes [14], [12], mapping of repetitive DNA sequences [15], and inferences of karyotype evolution [10–11].…”
Section: Introductionmentioning
confidence: 99%